DYNAMIC BEHAVIOR OF METHANE IN CONFINED SPACES BY CFD SIMULATION - Lâutaru, Vlad; Simion, Alexandru; Munteanu, Laurentiu (International Multidisciplinary Scientific GeoConference SGEM, 2024)
Gases released because of accidents and events that cause the contamination of certain indoor spaces with methane have become more frequent recently. These gases endanger the lives of people who are inside the contaminated spaces, and there is a need for more and more in-depth research on the dynamic behavior of certain substances with a toxic effect, such as methane, once it begins to accumulate in a closed space, for to develop new detection systems and especially for its evacuation in the shortest possible time from the contaminated space. In this sense, in the paper we analyzed the dynamic behavior of the gas with a toxic and explosive effect, namely methane, through a CFD computer simulation, in a closed space, to analyze the mode and duration of the distribution of methane concentration. To perform the CFD simulation, the physical conditions of a closed space of 50 m2, and with a methane volume of 418.5 liters, were replicated, and the duration of the simulation was 93 minutes. Following the analysis, we developed a technical solution to prevent the spread of methane in closed spaces following an accident/event.